Antidiabetics and antihypertensive medications use in Morocco: A pharmacoepidemiological descriptive study - Elyamani Rida; Abdelmajid Soulaymani; Zineb Serhier; Hinde Hami; Mokhtari Abdelrhani (AOSIS, 2020)
Background: In Morocco, and many other African countries, there is a paucity of antihypertensive and antidiabetics use amongst the general population. Aim: To investigate the epidemiological profile of antihypertensive and antidiabetics use and analysis their adverse reactions. Setting: This study was conducted in the prefecture of Figuig, Morocco. Methods: A cross-sectional descriptive study. Data was collected using semi-structured questionnaire about their pharmacological treatment and presented using descriptive statistical analysis. Results: Sample of 244 subjects, predominantly women 58.15% (p 0.03) composed of diabetic patients 56.96% (n = 139) and hypertensive patients 43.03% (n = 105). After adjustments, 60.24% of all patients were under monotherapy. The diabetics were being treated using the Biguanide class (26.92%), insulin (20.0%) and sulfonylureas (10.0%) while hypertensive patients were treated by Calcium Channel Blockers (27.36%), Angiotensin Converting Enzyme Inhibitors (21.05%), Angiotensin T-Blockers (16.84%), Diuretics (7.36%) and β-adrenergic receptors blockers (3.15%). In total, 23.00% of all subjects have experienced negative side-effects, mostly, reported (90.38%) to health professionals and 23.52% of them have interrupted temporarily or try to change their treatment. Gastro-intestinal problems were the most adverse reactions reported (11.11%) followed by headache, dizziness and tinnitus (6.66%) and asthenia, feeling sick and feeling of faintness (5.33%). Conclusion: Managing diabetes and hypertension entails a lot of public challenges and requires more focus and interest, especially amongst the illiterate population in remote areas. Some of the suggested ways to help face the problem include the introduction of new innovative measures, systems of fellow-up and adverse reactions.